Hybrid Architectures for Machine Translation Systems. - Thurmair, Gregor (Language Resources & Evaluation, 2005)
Although some progress has been made on the quality of Machine Translation in recent years, there is still a significant potential for quality improvement. There has also been a shift in paradigm of machine translation, from “classical” rule-based systems like METAL or LMT towards example-based or statistical MT. It seems to be time now to evaluate the progress and compare the results of these efforts, and draw conclusions for further improvements of MT quality. The paper starts with a comparison between statistical MT (henceforth: SMT) and rule-based MT (henceforth: RMT) systems, and describes the set-up and the evaluation results; the second section analyses the strengths and weaknesses of the respective approaches, and the third one discusses models of an architecture for a hybrid system.